The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/hypertensionaha.111.176602
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Enhanced Vascular Reactivity in Preeclampsia

Abstract: Preeclamptic women have enhanced blood pressure response to angiotensin II and extensive systemic vascular infiltration of neutrophils. Neutrophils release reactive oxygen species that might activate the RhoA kinase pathway to enhance vascular reactivity. We hypothesized that enhanced vascular reactivity in preeclampsia is due to neutrophil mediated reactive oxygen species activation of the RhoA kinase pathway. Omental arteries were obtained at cesarean section and studied using a myograph system. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…An abundant literature exists on oxidant molecules associated with pre-eclampsia (48). RNS and ROS stresses are generally treated as a whole (17).…”
Section: Discussionmentioning
confidence: 99%
“…An abundant literature exists on oxidant molecules associated with pre-eclampsia (48). RNS and ROS stresses are generally treated as a whole (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress with H 2 O 2 has been suggested to mediate airway smooth muscle contraction by increasing intracellular Ca 2+ level and stimulating the Rho/Rho kinase pathway (Snetkov et al 2011). Mishra et al (2011) reported also that enhanced vascular reactivity of omental arteries in pre-eclampsia is attributed to ROS activation of the RhoA kinase pathway, and that the enhanced vascular reactivity is likely attributed to the infiltration of neutrophils. In addition, Shimokawa (2000) and colleagues revealed that RhoA and its downstream effector, Rho kinase, are involved in the hypercontraction of vascular smooth muscle of the coronary artery in vasospastic angina, which is probably mediated by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…An excessive activation of neutrophils and monocytes in PE patients (circulating and in the decidua) have been described by many groups (21–26). These monocytes have been found to spontaneously synthesize greater amounts of pro-inflammatory cytokines such as IL-1b, IL-6, and IL-8 (27).…”
Section: Preeclampsia Development and The Immune Systemmentioning
confidence: 99%